Comparative Study of Growth Statistics of Two Species of Paulownia and Optimization of Rooting Methods - Saiju, Hari Krishna; Bajracharya, Abhishesh; Rajbahak, Brishav; Ghimire, Stuti (Nepal Journal of Biotechnology, 2019)
Paulownia is a fast-growing woody tree, native to the forests of China. It belongs to the family Scrophulariaceae and is mainly used as a source of wood for furniture and musical instruments. Due to its fast-growing nature and high-quality of wood, there has been growing interest in cultivation and research of Paulownia in Nepal. Growth comparison was performed by measuring shoot length in in vitro condition. Among two species of Paulownia - Paulownia tomentosa (Thunb.) Steud and Paulownia fortuneii (Seem.) Hemsl., the growth rate of P. tomentosa was found to be 0.355 cm/week while that of P. fortuneii was found to be 0.637 cm/week in in-vitro conditions in MS medium supplemented with 0.1 mg/l NAA and 1mg/l BAP. Optimization of rooting methods was also performed, in which, sand rooting was found to be easier and more effective than in-vitro rooting. Dipping the plantlets in 1 mg/l of NAA was found to produce longer and denser roots than lower or higher concentrations during sand rooting.